The complete mitochondrial genome of Tenguna medogensis (Hemiptera: Dictyopharidae) - Fang Yu; Zhi-Shun Song (Mitochondrial DNA. Part B. Resources)
In this study, we sequenced and annotated the complete mitochondrial genome of Tenguna medogensis Song & Liang, 2007 (Hemiptera: Dictyopharidae). The mitogenome was 15,400 bp in length with a high A + T content (76.95%), containing 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. All protein-coding genes started with ATC/ATG/ATT, except for nad1 and nad5, which used GTG. The predicted secondary structures of all tRNA genes were typical cloverleaf except for trnS (gcu) and trnV (uac), lacking the dihydrouridine stem. In the maximum-likelihood phylogenetic result of planthoppers, Tenguna was closely related to Metaurus in Dictyopharidae.